The Influence of Cutting Roots on the Growth and Fruiting of ‘Top Group’ Plum Cultivars - Viorel MITRE; Andreea ANDRECAN; Sabin MOLNAR; Maria CODREA; Vasile MELNIC; Lehel LUKACS; Berta Ştefania MOLNAR (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Horticulture, 2019)
The influence of cutting roots on the growth and fruiting of ‘top group’ plum cultivars (‘Topfirst’, ‘Topfive’, ‘Toptaste’, ‘Tophit’ and ‘Topend Plus’), under the pedoclimatic conditions of Sînmihaiu Almasului, in the centre of Transylvania, Romania, in 2017-2018, was studied. The trees were grafted on Saint Julien rootstock, trained as Zahn Spindel and the orchard had a density of 1000 trees/ha. Roots were cut twice, at 40 cm distance from the trunk, in an angle of 45° and 30 cm depth, as followed: first time in the autumn during the fall of leaves, on one side of the row and the second time in spring, at blooming time, on the other side of the row. The measurements were done each year after the leaves have been fallen. There were made observations on some growth parameters (length of shoots, height of trees, trunk sectional area, the fruits and vegetative branches ratio) and fructification (average yield for 2017-2018 period, and was determined the productivity index). The treatments influenced the shoot growth, height of the trees, cumulative yield, trunk cross sectional area, the ratio of the yield to a trunk sectional area, with differences statistically assured. Root pruning reduced the average length of shoots. The longest shoots, in mean values, gave the unpruned root variant (131.0 cm). Root pruning decreased the average length of annual growth (51.1 cm). The biggest average trunk cross sectional area with the unpruned root system was obtained (58.7 cm2). Also root pruning influenced the height of the trees. The best cumulative yield was obtained in the variant of root pruning system (28.75 t/ha) followed by the unpruned root system (25.87 t/ha). Finally, root pruning increased productivity. The biggest value was registered in ‘Tophit’ in the root pruned variant (0.73 kg/cm2). The lowest value of productivity index was obtained in the unpruned system.